Los efectos distributivos de la ley 70 de 1993 : el caso de afrosiso (2021)
This article studies the distributive effects derived from the right to common property contained in Law 70 of 1993. To this end, it analyzes the case of a Community Council located in La Sierra (Cauca) whose autonomy and permanence in the territory are threatened by the arrival of an energy project. In order to understand the case as a distribution issue, it brings up the postulates of environmental justice. From the proposed analysis, it concludes that, although this law has meant incremental gains for the communities, it has not represented a true redistribution in their favor because it has not allowed them access to full ownership of the lands they have occupied and the organizational forms it recognizes are not endowed with sufficient resources to establish themselves as true political organizations capable of making decisions about the territory. Finally, it suggests some normative adjustments aimed at strengthening the Community Council's capacity to negotiate.